A scoping review of therapeutic mentoring for youth mental health - Werntz, Alexandra; Rhodes, Jean E.; Brockstein, Hannah; Fallon, Lindsay; Cook, Amy (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionTherapeutic mentoring, which leverages paraprofessional care, is a potential way to scale access to care to address the youth mental health crisis. This scoping review synthesizes the current state of research on self-designated therapeutic mentoring programs for youth mental health.MethodA systematic search was conducted across four databases using the term “therapeutic mento*” and related keywords, taking a label-first approach to describe the available literature. Inclusion criteria were peer-reviewed articles about research on therapeutic mentoring in the US, written in English. Data were extracted on study characteristics, intervention details, mentor background, and outcomes.ResultsEighteen empirical articles were identified, published between 2003 and 2024. Most studies focused on at-risk youth from diverse backgrounds. Therapeutic mentoring programming varied, although most (N = 13) studies examined the Campus Connections program. Mentors were typically trained paraprofessionals or undergraduate students supervised by clinical professionals. Only two randomized controlled trials were found, both of the Campus Connections program.DiscussionThe review revealed a lack of rigorous experimental studies on therapeutic mentoring efficacy, as defined by studies that use the term therapeutic mentoring. While some studies showed promising effects, more research is needed to establish the definition of therapeutic mentoring and whether it is an acceptable and effective intervention for youth mental health.ConclusionA clear definition of therapeutic mentoring is needed to advance the field and facilitate systematic evaluation of its effectiveness in supporting youth mental health. Future research should prioritize developing program models that align with diverse youth's cultural values, conducting randomized controlled trials, examining program components, and developing standardized measures for assessing therapeutic mentoring outcomes.